“A right kind of rogue”: Lisa McInerney’s The Glorious Heresies (2015) and The Blood Miracles (2017) - Ostalska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2019)
The following article analyzes two novels, published recently by a new, powerful voice in Irish fiction, Lisa McInerney: her critically acclaimed debut The Glorious Heresies (2015) and its continuation The Blood Miracles (2017). McInerney’s works can be distinguished by the crucial qualities of the Irish Noir genre. The Glorious Heresies and The Blood Miracles are presented from the perspective of a middle-aged “right-rogue” heroine, Maureen Phelan. Due to her violent and law-breaking revenge activities, such as burning down the institutions signifying Irishwomen’s oppression (i.e. the church and a former brothel) and committing an involuntary murder, Maureen remains a multi-dimensional rogue character, not easily definable or even identifiable. The focal character’s narrative operates around the abuse of unmarried, young Irish mothers of previous generations who were coerced to give up their “illegitimate” children for adoption and led a solitary existence away from them. The article examines other “options” available to “fallen women” (especially unmarried mothers) in Ireland in the mid-twenty century, such as the Magdalene Laundries based on female slave work, and sending children born “out of wedlock” abroad, or to Mother and Baby Homes with high death-rates. Maureen’s rage and her need for retaliation speak for Irish women who, due to the Church-governed moral code, were held in contempt both by their families and religious authorities. As a representative of the Irish noir genre, McInerney’s fiction depicts the narrative of “rogue” Irish motherhood in a non-apologetic, ironic, irreverent and vengeful manner.